Development of Laboratory Equipment Inventory System Using Radio Frequency and Internet of Things - Mochamad Fajar Wicaksono; Syahrul Syahrul; Myrna Dwi Rahmatya (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
The purpose of this research is to create a laboratory equipment inventory system. With this system, users, namely lecturers, lab assistants, and final project students, can find out the borrower's data, borrowing time, return time, and the tool availability status. The research method used is experimental. This system is based on IoT technology. The main brain from the hardware side uses the NodeMCU ESP8266. NodeMCU, apart from being a controller, can also function as a WiFi module. On the server-side, PHP and MySQL are used. When the user wants to borrow a tool, the user can use an RFID tag to open the cupboard. Furthermore, the NodeMCU will continue to scan for the presence of items in the cupboard using a radio frequency with RF433MHz. This information is sent to the server when the cupboard is closed and locked automatically. The server will receive the information and decipher the information. As a result, the testing process in this study proved that the system has been able to detect the presence of items in the cupboard and track anyone who borrows laboratory equipment with a 100% success percentage.